PEMIKIRAN MANUSIA DALAM ALIRAN – ALIRAN FILSAFAT - Rosita Baiti (Wardah, 2015)
Human thought in the process of  identity searching is never known the word “tired, or exhausted, to keep on fantasizing, hallucinating, or experimenting in showing genius ideas of  that still exist in order to create  benefits value and a drop of oasis for the happiness of human life that are living under the planets and layers of Earth's atmosphere. Human thought is doing metamorphoses  in philosophy without knowing the barriers, through space and time, it could be so riveting from time to time. Along this, without exception, the differences of human interpretation in perceiving the ideas develop into parts of philosophy. Undoubtedly, it should be recognized that every people, tribe, race, or nation in the world, has a philosophy and life -principle differently, in line with the philosophy of life which are adopted, and believed respectively. Then philosophy summarizes human mind into parts of philosophy. This article will reveal briefly, human thought about the parts of philosopy (aliran).